Effects of Ti Microalloying on the Microstructure and Mechanical Properties of a Novel GH1059 Alloy for Nuclear Applications - Wang Jiaqi, Yao Zhiqiang, Wu Jinrong, Guan Xianjun, Wu Yunsheng, Zhao Le, Qin Xuezhi, Zhou Lanzhang (Teshugang)
The influence of Ti microalloying on the microstructure and mechanical properties of a novel Fe-Ni-based superalloy GH1059 with high-strength， high-toughness and long-life for fast reactors was investigated using SEM， EBSD， and TEM. The results showed that the addition of Ti significantly increased the amount of Ti-rich MC carbides， which precipitated in a finer and more dispersed manner， while effectively suppressing the formation of M23C6 carbides at grain boundaries （GBs）. With increasing Ti content， the average grain size of the alloy gradually decreased， while the fraction of low-Σ coincidence site lattice （CSL） boundaries remained largely unchanged. The results of 750 ℃ tensile and room temperature impact properties showed that Ti microalloying can simultaneously improve both strength and toughness. The tensile fracture mode was a mixed-mode fracture， and the deformed microstructure was mainly composed of dislocation cells and sub-grains. The improvement in mechanical properties were primarily attributed to solid-solution strengthening by Ti atoms， precipitation strengthening from TiC， grain refinement， and enhanced GB bonding force.